PRAKTIK GHARAR DAN TADLIS PADA TRANSAKSI E-COMMERCE DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH DAN RELEVANSINYA DENGAN HUKUM POSITIF - Kamil Rafi Muhammad; Muhammad Andy Prananto; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze practices that occur in the digital space that manifest in the form of gharar and tadlis in e-commerce transactions, and review their relevance to positive legal instruments in Indonesia. The research method used is normative juridical with a statute approach and a conceptual approach. Primary legal materials are sourced from the Qur'an, especially the five ahkam verses, the Consumer Protection Law (UUPK), and the Electronic Information and Transactions Law. The results of the study indicate that the practice of manipulating descriptions, fictitious reviews, and visual engineering of digital products are clear violations of the universal principles contained in the Qur'an, especially in the verses concerning the prohibition of measurement fraud as analogous to QS. Al-Mutaffifin verses 1-3, betrayal of trust in QS. An-Nisa verse 58, and the destruction of the essence of willingness or antaradhin in QS. An-Nisa verse 29 which has implications for the invalidity of assets obtained by business actors illegally according to QS. Al-Baqarah verse 188. In addition, fulfilling product specification promises is an absolute obligation according to the command of QS. Al-Ma'idah verse 1 which provides the right of khiyar for consumers who are harmed. This study also concludes that the positive legal instruments in the Consumer Protection Law and the Electronic Transaction Information Law have a very strong level of synergy with the principles of Sharia Economic Law in an effort to protect consumers' property ownership rights (hifzh al-mal) through enforcing the values ​​​​of transparency and honesty of information in the digital era. This harmony between state law and religious law creates a comprehensive legal protection shield to eradicate all forms of transaction manipulation in the electronic commerce ecosystem so that it continues to run according to the corridor of justice for the parties involved in digital sales and purchase agreements.